Homogenization of Macroinvertebrate Assemblages and Asiatic Clam Corbicula fluminea Invasion in a River of the Arid Patagonian Plateau, Argentina - Labaut, Yeny; Macchi, Pablo A.; Archuby, Fernando M.; Darrigran, Gustavo (Frontiers in Environmental Science, 2021)
The invasion of the Asiatic clam Corbicula fluminea in South America has already reached Patagonia. Despite the well-known direct and indirect impacts that this species exerts on fresh-water ecosystems, particularly on benthic communities, few studies have been undertaken on its effect on the composition and structure of aquatic macroinvertebrate assemblages. This study evaluated the effects of the invasion of the Asiatic clam C. fluminea on the aquatic macroinvertebrate assemblages of the Limay River, one of the most important rivers of the arid plateau of Argentinian Patagonia. As this river is currently in the process of being invaded, it was possible to compare invaded and non-invaded sites. Invaded sites displayed a certain homogenization of their constituent species and functional composition. Non-metric multidimensional scaling, similarity analysis and similarity percentages showed negative or positive influence of the presence of this species on the abundance of some taxa, due to competition for resources in this low-productivity Patagonian ecosystem. The deposition of the faeces and pseudo-faeces of C. fluminea enriches the organic content of the sediments. However, its pedal feeding can function as a competitive strategy: by consuming its own deposited organic matter when food is scarce, the amount available to other macroinvertebrates is reduced. This paper is the first contribution on the impact of this invasion on northern Patagonia’s aquatic macroinvertebrate assemblages.